Wacana KTT G20 Bali dalam Perspektif Metafora Konseptual - Ritonga, Ovi Andre; Mulyadi, Mulyadi; Lubis, Rosliana (Innovative: Journal Of Social Science Research, 2025)
This study describes the semantic categorization and conceptual mapping of metaphors contained in the discourse of the Bali G20 Summit in online mass media. The data used are written data. The data of this study were obtained using the listening method and note-taking technique. The data were analyzed using the distribution method with the basic technique being the direct element sharing technique (BUL). This study uses the Conceptual Metaphor theory by developing image-schemes as an analysis tool. The results obtained were that two types of metaphors were found, namely ECONOMIC metaphors and TECHNOLOGY metaphors. In the TECHNOLOGY metaphor, seven categories were found, namely, (1) PHYSICAL POWER, (2) VEHICLES, (3) DISEASES, (4) TRAVEL, (5) PLANTS, (6) ENEMIES, and (7) POWER. In the ECONOMIC metaphor, seven categories are found, namely, (1) PLANTS, (2) VEHICLES, (3) NATURAL POWER, (4) BODY ANATOMY, (5) BUILDINGS, (6) DISEASES, and (7) PHYSICAL POWER. In the conceptual mapping of the TECHNOLOGY metaphor, there is a SPACE scheme. Meanwhile, in the conceptual mapping of the ECONOMIC metaphor, there is a SOURCE-PATH-GOAL scheme, a POWER scheme, and a SPACE scheme.